2009
DOI: 10.1590/s1517-83822009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Screening of different fungi for decolorization of molasses

Abstract: The decolorization of molasses by 17 different fungi in 2 media was studied. Trichoderma viride showed the highest decolorization yield (53.5%) when cultivated at 30ºC for 7 days in Medium 1 which contained the molasses which was diluted to 40 g/L in distilled water. The other Trichoderma species and Penicillium sp. also gave similar results of 40-45%. Decolorization yield was increased by adding peptone and yeast extract to the production medium except Penicillium sp. Growth rate was not related to decoloriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Experiment was repeated with the optimized parameters and COD reduction with residual color was observed. The observance was measured as decrease in optical den sity of supernatant of treated ADSW medium at 475 nm (Krishna Prasad et al, 2009;Seyis, et al, 2009) on UV Spectrophotometer (Perkin Elmer Model: Lambda 35). pH determination was made by using Digital portable pH meter (Model pt-10P, Sartorius).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiment was repeated with the optimized parameters and COD reduction with residual color was observed. The observance was measured as decrease in optical den sity of supernatant of treated ADSW medium at 475 nm (Krishna Prasad et al, 2009;Seyis, et al, 2009) on UV Spectrophotometer (Perkin Elmer Model: Lambda 35). pH determination was made by using Digital portable pH meter (Model pt-10P, Sartorius).…”
Section: Methodsmentioning
confidence: 99%
“…In case of decolorization of molasses Trichoderma species it was concluded that enzymes formed by fungi during the process were effective only in acidic conditions. (Seyis et al, 2009) An increase in color at high pH was due to the polymerization of melanoidins and higher nutrient utilization. However, overall significant decolorisation was obtained in the optimal range of 5-6 which confirms the significant rol of pH in color removal.…”
Section: Effect Of Ph On Color Removalmentioning
confidence: 99%
“…Melanoidin decolorization was studied at different range of pH (3.0-7.0) by various workers and have reported that enzymes formed by microorganism during the decolorization was effective only in acidic conditions (Seyis and Subasing, 2009). At high pH, increase in the color was due to the polymerization of melanoidins and higher nutrient utilization (Adikane et al, 2006;Jiranuntipon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Biomass production was evaluated by determining the dye mass of the mycelia. Mycelia were harvested from the cultivation liquid medium by filtration using filter paper, dried at 50°C overnight until a constant weight was achieved, and then weighed (Abedin 2008;Maximo et al 2003;Seyis and Subasioglu 2009).…”
Section: Decolorization Studies In Batch Liquid Mediummentioning
confidence: 99%
“…Some dyes are toxic, mutagenic, carcinogenic, or allergenic (Bakshi et al 1999). It is estimated that about 10-15% of dyes are released into processing water (Selvam et al 2003;Shakibaie et al 2008;Seyis and Subasioglu 2009;Singh and Singh 2010).…”
Section: Introductionmentioning
confidence: 99%